Mysterious discoloration of nails in both hands, particularly thumbs alone: a curious case of varied pigmentation in both hands - Akshay Kumar Jain; Shivani Saini (Wolters Kluwer Medknow Publications, 2023)
Preterm babies have immature immunity and skin barrier functions. To cope up with these, many times they are kept under observation in neonatal care unit (NICU) for months until they attain their normal physiological age, weight, and immune functions along with other vital capacities. We are reporting such a curious case of 1-month-old preterm child who presented with the sequence of blackish blue to yellowish discoloration of thumb nails in both the hands.